I dispersion in Argentina: Concentrations in fresh and marine water and deposition fluences in Patagonia - Negri, Agustin Eduardo; Fernandez Niello, Jorge Oscar; Wallner, Anton; Arazi, Andres; Fifield, Leslie K.; Tims, Stephen G. (Environmental Science & Technology)
Measurements of total iodine (I) and iodine-129 (129I) concentrations in rivers and lakes of Argentina are presented. Their latitudinal distribution can be explained by taking into account their main sources (oceanic emissions and biomass burning for I, and atmospheric nuclear tests for 129I), transport mechanisms, and fallout patterns. From the measured 129I concentrations in the studied lakes, deposition fluences for their catchment areas were estimated. These results agree with a model of the global deposition pattern due to the 129I released by atmospheric nuclear weapon tests and with other fluences reported for the southern hemisphere. In addition, the first measurements of 129I in shallow seawater from the South Atlantic Ocean are presented and discussed. Fil: Negri, Agustin Eduardo. Comisión Nacional de Energía Atómica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Fernandez Niello, Jorge Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comisión Nacional de Energía Atómica; Argentina. Universidad Nacional de San Martín; Argentina Fil: Wallner, Anton. The Australian National University; Australia Fil: Arazi, Andres. Comisión Nacional de Energía Atómica; Argentina Fil: Fifield, Leslie K. The Australian National University; Australia Fil: Tims, Stephen G. The Australian National University; Australia